2018
DOI: 10.1186/s12931-018-0802-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of adipose-tissue-derived mesenchymal stromal cells and their extracellular vesicles in experimental silicosis

Abstract: BackgroundSilicosis is an occupational disease that affects workers who inhale silica particles, leading to extensive lung fibrosis and ultimately causing respiratory failure. Mesenchymal stromal cells (MSCs) have been shown to exert therapeutic effects in lung diseases and represent an alternative treatment for silicosis. Recently, it has been suggested that similar effects can be achieved by the therapeutic use of extracellular vesicles (EVs) obtained from MSCs. The aim of this study was to investigate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 57 publications
1
34
1
Order By: Relevance
“…In addition, these vesicles are engulfed and reutilized by macrophages and MSCs simultaneously shed miRNA-containing exosomes that inhibit macrophage activation by suppressing Toll-like receptor signaling (MyD88-dependent), thereby desensitizing macrophages to the ingested mitochondria [ 83 ]. Furthermore, Bandeira et al reported that mouse AD-MSCs and their EVs ameliorated pulmonary fibrosis and inflammation in a late-stage model of silicosis [ 84 ]. Interestingly, EV treatment at the higher concentration yielded outcomes comparable with those observed by MSC treatment in this study, promoting enhanced impacts on lung mechanics and macrophage infiltration [ 84 ].…”
Section: Mesenchymal Stem Cell-derived Extracellular Vesicle-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these vesicles are engulfed and reutilized by macrophages and MSCs simultaneously shed miRNA-containing exosomes that inhibit macrophage activation by suppressing Toll-like receptor signaling (MyD88-dependent), thereby desensitizing macrophages to the ingested mitochondria [ 83 ]. Furthermore, Bandeira et al reported that mouse AD-MSCs and their EVs ameliorated pulmonary fibrosis and inflammation in a late-stage model of silicosis [ 84 ]. Interestingly, EV treatment at the higher concentration yielded outcomes comparable with those observed by MSC treatment in this study, promoting enhanced impacts on lung mechanics and macrophage infiltration [ 84 ].…”
Section: Mesenchymal Stem Cell-derived Extracellular Vesicle-basedmentioning
confidence: 99%
“…Furthermore, Bandeira et al reported that mouse AD-MSCs and their EVs ameliorated pulmonary fibrosis and inflammation in a late-stage model of silicosis [ 84 ]. Interestingly, EV treatment at the higher concentration yielded outcomes comparable with those observed by MSC treatment in this study, promoting enhanced impacts on lung mechanics and macrophage infiltration [ 84 ].…”
Section: Mesenchymal Stem Cell-derived Extracellular Vesicle-basedmentioning
confidence: 99%
“…They also demonstrated that the IV injection of MSC-derived EVs in the lung of silica-exposed mice reduced lung inflammation and the fibrotic response. Bandeira and colleagues demonstrated that intratracheal installation of adipose MSC-derived EVs in a silicosis mouse model led to a reduction in collagen deposition, granuloma size, and macrophage influx [51]. Furthermore, they showed a reduction in the expression of Interleukin 1β and transforming growth factor β.…”
Section: Silicosismentioning
confidence: 99%
“…In inflammatory cells, surface CD107a reflects the state of activation ( Janvier and Bonifacino, 2005 ) and has been implicated in cell adhesion ( Kannan et al, 1996 ; Min et al, 2013 ). In separate reports, CD107a has been described in intracellular vesicles in both osteoblasts and adipocytes ( Bandeira et al, 2018 ; Solberg et al, 2015 ), yet beyond this, essentially nothing is known regarding CD107a in mesenchymal stem cell fate or differentiation decisions.…”
Section: Introductionmentioning
confidence: 99%